Nanostructure-Induced Thermoelectric Enhancement in Bi₂Te₃ Nanorods Design, Analysis, and Performance Evaluation - Anish Kumar (International Journal of Energy and Thermal Applications, 2026)
Thermoelectric materials capable of efficient energy conversion near room temperature are critical for waste heat recovery applications. In this work, solution-grown Bi₂Te₃ nanorods were synthesized via a trioctylphosphine-assisted thermal decomposition route, and the influence of surfactant-induced nanostructuring on their thermoelectric properties was systematically investigated. Structural analysis using X-ray diffraction and Rietveld refinement confirmed the formation of rhombohedral Bi₂Te₃ with the emergence of Bi₂Te₃–BiTe nanocomposites at higher surfactant concentrations. Electron microscopy revealed one-dimensional nanorods with crystallite sizes tunable down to ~40 nm. Raman spectroscopy showed the appearance of IR-active A₁u modes, indicating a ligand-induced breakdown of inversion symmetry due to the formation of sub-quintuple layers along the nanorod axis. Thermoelectric measurements demonstrated n-type conduction with a significant enhancement in Seebeck coefficient attributed to carrier energy filtering at grain boundaries and quantum confinement effects. An optimized surfactant concentration yielded a maximum power factor of 348.7 μW m⁻¹ K⁻² at 300 K, exceeding values reported for comparable solution-processed Bi₂Te₃ systems. The combined effects of reduced crystallite size, controlled barrier height, and nanocomposite formation establish surfactant-engineered Bi₂Te₃ nanorods as promising candidates for high-performance near-room-temperature thermoelectric applications.
Keywords: Bi₂Te₃ nanorods; Energy filtering; Solution growth; nanocomposites; thermoelectric materials